Pharmacology - Whalen, Karen; Finkel, Richard (Richard S.); Panavelil, Thomas A. (Lippincott's illustrated reviews., 2015)
Lippincott Illustrated Reviews: Pharmacology, Sixth Edition, is the updated, enhanced version of the student-favorite resource for essentials of medical pharmacology. The first-and-best resource, the Lippincott Illustrated Reviews series features clear, effective writing and hundreds of illustrations for ideal rapid review and the assimilation of complex information. Clear, sequential images present mechanisms of action and focus on showing rather than telling students how drugs work.